In search of the Soviet prototype of the 10th Department of MPS (Ministry of Public Security) - Lityński, Adam (Studia Iuridica Toruniensia, 2024)
In 1948, Poland was considered a political purge. This happened at the command of Stalin from Moscow also in other satellite states of the Union of Soviet Socialist Republics. In Poland, the purge was led by the leader of the communist party, i.e. the First Secretary of the Central Committee of the Polish United Workers’ Party – Władysław Gomułka, and his coworkers. A special team was appointed to carry out the purge of the MPS. This team soon became the 10th Department of the MPS. It was the 10th Department which kept the high-ranking communists under surveillance and made their arrests. Finally, the officers of the 10th Department were conducting the proceedings and, in practice, they decided on the verdicts. The author posed a scientific problem: was the Polish structure – the 10th Department of MPS – following the Soviet one? The author traced the structures of the authorities of the Union of Soviet Socialist Republics in the period from 1934 to 1953. For this purpose, the author included in his research the memories of one of the commanders of the Soviet security services – Pavel Sudoplatov, as well as the son of Lavrentiy Beria, the head of the Soviet security service for 15 years (1938–1953) and the second most important person after Stalin. The author used in his research the diaries of the NKVD general Ivan Sierov, who, on Stalin’s orders in 1944–1945, organized a special brutal pacification of Poland and organized the Polish MPS. The final conclusion is that in the USSR, there was no such structure as there was after 1948 in Poland.